Integritas Kepemimpinan Dalam Gereja Berdasarkan Yakobus 3:16: Kepentingan dan Tantangan - Royke Lantupa Kumowal (STT IKSM SANTOSA ASIH, 2026)
Interest-based politics within the church has become an increasingly evident phenomenon that weakens congregational relationships, reduces trust in leadership, and shifts ministry orientation from spiritual mission toward group interests. This study aims to examine interest-based politics in the church based on James 3:16 and to explain its challenges to servant leadership. The research employs a qualitative approach using a library research design. The primary source is the biblical text of James 3:16, while secondary sources include scholarly books, journals, and articles related to church conflict and leadership. Data were collected through literature review and analyzed descriptively and qualitatively through processes of reduction, interpretation, and synthesis. The findings reveal that James 3:16 identifies envy (zēlos) and selfish ambition (eritheia) as the moral-spiritual roots that generate disorder (akatastasia) and various unhealthy practices within the faith community. In contemporary church contexts, these roots are manifested in interest-based politics that distort ministry motivation, damage congregational relationships, and create a crisis of spiritual legitimacy for leaders. This study concludes that interest-based politics in the church is not merely an organizational issue but a spiritual and communal problem that contradicts the principle of servant leadership. Therefore, churches need to strengthen transparency, accountability, leadership character formation, and effective conflict-resolution mechanisms to maintain ministry integrity and communal health.